"We open doors others do not!": Position and power of foreign institutional networks. Issue 3 (June 2022) - Ólafsdóttir, Bryndís; Kristjánsdóttir, Erla S.; Freeman, Susan
Abstract: Foreign institutional actors (INAs) can act as a liaison between firms and authorities and other power players to navigate bureaucratic structures, both as resource and legitimacy providers in the host market. Building on institutional theory, this study draws from broader organizational sociological literature, to explore the structural position of INAs in a host country context, and engages with fundamental questions of legitimacy, status, and power. It responds to repeated calls that more studies in international business research are needed on the impact of institutional differences, how to obtain legitimacy, and enhance the home country support networks. To understand INAs' position, specifically within the social structure of a bureaucratic host environment, our study uses in-depth interviews with elite actors from the support networks. Japan is chosen for this study as a host market, because it is the European Union's second largest trading partner in Asia, has a strong central bureaucracy, and historically and currently remains a challenging market for Westerners due to complex market entry barriers. The findings provide a new theoretically derived empirical model demonstrating the positional leverage of these INAs, to "open-doors" into a complex environment and offer a nuanced understanding of their formal and informal structural positions of power. The findings also demonstrate a significant overlap between organizational legitimacy and the exemplary status of these INAs in the bureaucratic environment, which enhances and empowers their leverage to reach authorities, press, and other important actors in the market.